Evaluation of cleft lip and palate frequency and related risk factors in infants born in Kermanshah hospitals (2001-2008) - Mansour Rezaei; Somaieh Ghanbari; Mozafar Khazaei; Ali Asghar Alipour; Saber Khazaei (Isfahan University of Medical Sciences, 2011)
Introduction: Cleft lip and palate are the most common congenital anomalies in the head and neck region, which are affected by environmental and genetic factors. The prevalence of these anomalies varies in different countries. There is no scientific report from the west of Iran. The aim of the present study was to determine its prevalence and related risk factors in infants born in Kermanshah hospitals during 2001-2008.Materials and methods: In this descriptive study, 62823 infants born during 2001-2008 in Motazedi and Imam Reza hospitals in Kermanshah (a city in the west of Iran) were reviewed. A total of 98 cases with oral clefts were recorded. Data were analyzed by ANOVA and Chi-square test using SPSS12 statistical software.Results: Out of 62823 infants 98 cases had oral clefts (1.5 for 1000 birth), 59.8% of which were males; 38.8% had cleft lip and palate; 31.6% had cleft lip and 29.6% had cleft palate. A total of 51.3% of parents had familial marriage; 14.7% of mothers reported use of medications; 40% of mothers had A+ blood group; 37.2% of the newborns were the first baby of the family and 93.8% of mothers had not taken vitamin supplements. The mean age of mothers were 27 years and the highest number of clefts belonged to 21-30 year-old mothers.Conclusion: The prevalence of oral clefts and their types in Kermanshah are consistent with world reports but lower than the calculated average for Iran.Key words: Cleft lip, Cleft palate, Prevalence, Maternal age, Blood group.